Forensic Linguistic Analysis of Critical Speech in the Haris Azhar & Fatia Video: Between Freedom of Expression and Defamation - Hadiwijaya, Munawwir; Sunuyeko, Nurcholis; Yahmun, Yahmun (UIBU, 2025)
This article examines the speech delivered in a YouTube video by Haris Azhar and Fatia Maulidiyanti, which led to a defamation lawsuit filed by a high-ranking Indonesian official. Using a forensic linguistic approach, the study investigates whether the utterances constitute defamatory speech or protected public criticism. A descriptive qualitative method is employed to analyze the lexical, syntactic, pragmatic, and discourse-level features of the video. The analysis identifies three categories of speech—false factual claims, critical opinions, and data-driven statements—and finds that the utterances fall primarily within the latter two, characterized by cautious language such as “allegedly” and “according to reports.” These linguistic mitigations indicate a lack of intent to defame and reflect research-based criticism. The study concludes that the speech acts, from a forensic linguistic perspective, do not fulfill the criteria for criminal defamation, but rather exemplify constitutionally protected freedom of expression.